DINAMIKA FORMULASI KEBIJAKAN PRODUK HUKUM DAERAH (Studi Tentang Peraturan Daerah Provinsi Riau Nomor 1 Tahun 2012 Tentang Lembaga Adat Melayu Riau) - Yusnibar "; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
One of the functions of the Legislative Council is a legislative function, which together form the Regional Regulation of Governors. Formation of regulation can be done if there is a good proposal Draft Regulation initiative proposal of the Government and the Council. In this case the Riau Provincial Regulation No. 1 Year 2012 About the Institute of Traditional Malay proposed initiative is the Regional Legislative Board Riau Provincial Parliament.The discussion manuscript initiative by the Special Committee debate a tough experience, but with the spirit of togetherness and consensus agreement and uphold democracy, checks and balances to hold meetings with the Government of Riau Province, Commission A DPRD Riau Province in charge of Government and Law, Malay Customary Institution, Bureau law and Kesbangpol, academics / experts, in consultation with the Secretary General of the Bureau of legal Affairs, Chairman of the Board and fractions as well as study visits to areas that have regulations on customs, laws issued so beneficial to the public interest relating to the implementation and execution setting things which are not contrary to Regulation Legislation higher.This study uses qualitative and quantitative data collection techniques while using methods of observation, interviews and questionnaires, while data analysis was done descriptively. This study examines the formation of a regional regulation process in the Legislative Council Secretariat Riau Province.Based on the results of this study there are three key elements that must be passed in the establishment of a Regional Regulation of the preparation process, Process Discussion and Ratification Process. Each of the process the Board's role is crucial in the fight for the aspirations of the community in order to benefit the policy issued public interest.Keyword : Formulation of preparing legislation, discussion, ratification.